2022
DOI: 10.3390/jcm11143982
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular and Neuronal Changes Are Also Present, Even If Differently, in Adolescents with Type 1 Diabetes without Clinical Diabetic Retinopathy

Abstract: The purpose of this study was to evaluate retinal changes in adolescents with childhood-onset, long-lasting type 1 diabetes mellitus (T1D). Patients and healthy controls (HC) underwent optical coherence tomography (OCT) and OCT-angiography (OCTA). Individual macular layers, peripapillary retinal nerve fiber layer (pRNFL), and vascular parameters (vessel area density (VAD), vessel length fraction (VLF) and vessel diameter index (VDI)) of macular superficial vascular (SVP), intermediate (ICP), deep (DCP) and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Nevertheless, the literature is conflicting. A few studies showed early modification in the SCP [ 17 , 18 ], whereas others found retinal vessel rarefaction predominantly in the DCP [ 19 , 20 ]. The anatomy of the SCP corresponds with the vascularization lying in the nerve fiber layer and ganglion cell layer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the literature is conflicting. A few studies showed early modification in the SCP [ 17 , 18 ], whereas others found retinal vessel rarefaction predominantly in the DCP [ 19 , 20 ]. The anatomy of the SCP corresponds with the vascularization lying in the nerve fiber layer and ganglion cell layer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of the SCP corresponds with the vascularization lying in the nerve fiber layer and ganglion cell layer [ 21 ]. Recent studies have suggested that the neurovascular unit, including endothelial cells, pericytes, retinal neurons, and glial cells, is the primary site of early retinal changes, with a thinning of the nerve fiber and ganglion cell layers in type 1 diabetes even before the development of clinical diabetic retinopathy [ 18 ]. Another hypothesis is that the DCP is more challenging to analyze because of the deeper localization, thereby resulting in projection artifacts from superficial vessels that could lead to a less precise quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences exist in the cohorts of examined patients. For instance, Pilotto et al recruited adolescents with and without DR and found a reduced VD only in patients with clinical signs of DR [ 17 ]. In line with Pilotto, Golebiewska et al found no difference in VD between patients with type 1 diabetes without DR and healthy controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some methodological differences also emerge by comparing the studies. Indeed, Pilotto et al considered parafoveal and foveal areas when evaluating VD, and Golebiewska et al divided the retinal plexus into three layers [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation